2012
DOI: 10.1055/s-0032-1313102
|View full text |Cite
|
Sign up to set email alerts
|

Breast Microcalcifications as Type Descriptors to Stratify risk of Malignancy: a Systematic Review and Meta-Analysis of 10665 Cases with Special Focus on Round/Punctate Microcalcifications

Abstract: All suspicious type descriptors including round/punctate microcalcifications as well as combinations of type with suspicious distribution descriptors fell into BI-RADS assessment category 4. Exclusion of suspicious adjunct factors can direct clustered, round/punctate microcalcifications to a lower BI-RADS assessment category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 20 publications
0
38
0
3
Order By: Relevance
“…It has been reported that microcalcification can be seen in about 40-50 % breast carcinomas [14,15] and that DCIS usually appear as microcalcification on mammography [15]. Hypoechoic area with microcalcification was not mentioned in the previous guideline [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microcalcification can be seen in about 40-50 % breast carcinomas [14,15] and that DCIS usually appear as microcalcification on mammography [15]. Hypoechoic area with microcalcification was not mentioned in the previous guideline [6].…”
Section: Discussionmentioning
confidence: 99%
“…The management of BI-RADS 3 lesions continues to be controversial [13][14]. Several studies reported that patients with BI-RADS category 3 microcalcifications should undergo a biopsy procedure because of the high PPV (7%–8%) [15]–[16].…”
Section: Discussionmentioning
confidence: 99%
“…Con un valor p = 0,031 IC 95% (1,04 -16,61).Tener este tipo de calcificaciones representa un riesgo alrededor de 4 veces mayor en comparación al grupo que no las posee. Las características de las calcificaciones son descritas según la quinta edición del BI-RADS (15) ; sin embargo, uno de los controles fue descrito como calcificaciones sospechosas, termino parcialmente correcto, pues el hecho que sea sospechosa no significa que no debe describirse el tipo de calcificación. A su vez, la correlación de la presencia de algún tipo de calcificación sospechosa condiciona un grado de BI-RADS que va del 4 al 5, no siendo coherente en el sistema BI-RADS definir un caso con una calcificación sospechosa (gruesa heterogénea) como BI-RADS 0, evento que sucede en uno de los controles de este estudio (16) .…”
Section: Discussionunclassified